2014
DOI: 10.1007/s00294-014-0442-1
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Ebp2 and ribosomal protein L36 in ribosome biogenesis in Saccharomyces cerevisiae

Abstract: Ebp2 plays an essential role in biogenesis of 60S ribosomal subunits. We determined the genetic interactions between EBP2 and RPL36A/B, which encodes ribosomal protein L36a/b. RPL36A/B was a multicopy suppressor to ebp2 mutants, and the suppression was not common to defects in ribosome biogenesis resulting from other mutations of assembly factors. Disruption of RPL36A or RPL36B caused synthetic enhancement of the growth defect of the ebp2-14 allele at high temperatures. Disruption of RPL36B led to a more sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…In contrast, impairment of 27SA 3 and 27SB L pre‐rRNA processing, accompanied by the turnover of the downstream 27SB S and 7S S/L pre‐rRNA species, seems to be more specifically related to the depletion of L16. These pre‐rRNA processing defects closely resemble those described upon loss‐of‐function mutations in or depletion of different sets of 60S r‐subunit biogenesis factors: (a) the Pwp1 subcomplex (Pwp1, Nop12, Ebp2 and Brx1) , (b) the A 3 factors (Erb1‐Nop7‐Ytm1 subcomplex, Nop15, Nsa3, Rlp7, Rrp1) ( and references therein) and (c) Has1 , and upon depletion of distinct 60S r‐proteins including: (a) L8 and L36, which, together with L15, are close neighbours in a region of domain I of 25S/5.8S rRNA, where the 5′ end of 25S rRNA basepairs with the 3′ end of 5.8S rRNA and (b) L4, L6, L7, L18, L20, L32 and L33, which, together with L16 and L14 are clustered around domain II of 25S/5.8S rRNA . Decreased levels of 27SB S pre‐rRNA relative to 27SB L pre‐rRNA and absence of both 7S pre‐rRNA species have also been described upon depletion of L3 .…”
Section: Discussionsupporting
confidence: 60%
“…In contrast, impairment of 27SA 3 and 27SB L pre‐rRNA processing, accompanied by the turnover of the downstream 27SB S and 7S S/L pre‐rRNA species, seems to be more specifically related to the depletion of L16. These pre‐rRNA processing defects closely resemble those described upon loss‐of‐function mutations in or depletion of different sets of 60S r‐subunit biogenesis factors: (a) the Pwp1 subcomplex (Pwp1, Nop12, Ebp2 and Brx1) , (b) the A 3 factors (Erb1‐Nop7‐Ytm1 subcomplex, Nop15, Nsa3, Rlp7, Rrp1) ( and references therein) and (c) Has1 , and upon depletion of distinct 60S r‐proteins including: (a) L8 and L36, which, together with L15, are close neighbours in a region of domain I of 25S/5.8S rRNA, where the 5′ end of 25S rRNA basepairs with the 3′ end of 5.8S rRNA and (b) L4, L6, L7, L18, L20, L32 and L33, which, together with L16 and L14 are clustered around domain II of 25S/5.8S rRNA . Decreased levels of 27SB S pre‐rRNA relative to 27SB L pre‐rRNA and absence of both 7S pre‐rRNA species have also been described upon depletion of L3 .…”
Section: Discussionsupporting
confidence: 60%
“…Rrs1 and Rpf2 are involved in recruiting ribosomal proteins L11 and L5, and 5S rRNA into the pre‐60S ribosome (Nariai et al, ; Zhang et al, ). Ebp2 may play various roles in 60S ribosome biosynthesis, as it cooperates with the assembly factors Brx1, Pwp1 and Nop12, the ribosomal proteins L36, L34, L15 and L8 (Shimoji et al, ; Wan et al, ), the Mak5 cluster factors, Mak5, Rpf1 and Nop16, and ribosomal protein L14 (Pratte et al, ). We showed that Rrs1 and Ebp2 also localized to the nuclear periphery and these localizations were dependent on interaction with the N‐terminal region of Mps3, a SUN (for Sad1‐UNC‐84 homology) domain protein localized at the half‐bridge of the SPB, where the Mps3 is associated with the nuclear envelope.…”
Section: Resultsmentioning
confidence: 99%
“…Two of these were plasmids containing genes encoding the ribosomal proteins L36a and L34b. 4,5) Here, we determined that SMY2 also suppressed the growth defect of ebp2-14 ( Fig. 1(A)).…”
mentioning
confidence: 78%
“…2,3) To identify genes that are related to Ebp2, we previously screened for multi-copy suppressors that complement the temperature sensitivity of the ebp2-14 mutant (see supplemental Table S1 for yeast strains). 4,5) The ebp2-14 mutant was transformed with a library of yeast genomic DNA constructed in YEp24, 6) and five groups of plasmids were determined to be multi-copy suppressors. Two of these were plasmids containing genes encoding the ribosomal proteins L36a and L34b.…”
mentioning
confidence: 99%